Study of turbidity treatment in Karangpilang II Water Treatment Plant - Rahman, Arief; Masduqi, Ali (Sustinere: Journal of Environment and Sustainability, 2017)
Karangpilang II Water Treatment Plant (WTP) is a part of Karangpilang WTP of Surabaya Water Utilities that serves the water supply for Surabaya City. Karangpilang II WTP has the biggest clean water production capacity in Karangpilang WTP, which is 2500 L/s. Using conventional treatment to remove turbidity, the treatment plant in Karangpilang II WTP consists of pre-sedimentation, clearator and filter units. In this study, evaluation of turbidity quality in production water and turbidity removal efficiency were conducted to analyze the Karangpilang II WTP performance in turbidity treatment. The evaluation was conducted using the 2016 data, by comparing the turbidity of production water with the Water Quality Standard of the Water Utilities, and by comparing the turbidity of raw water, effluents of each treatment unit and production water. The evaluation result showed that in the case of Karangpilang II WTP turbidity removal performance, there were some occurrences that the turbidity in production water has not met the standard quality. The results also showed that there was a unit in the Karang Pilang II WTP with inadequate performance in turbidity removal, namely pre‑sedimentation unit. There are some solutions for the problem of turbidity removal in Karangpilang II WTP: increasing the maintenance schedule for pre-sedimentation unit; determining the proper turbidity reference in determination of coagulant dose; optimizing the coagulant dose; using produced sludge from water treatment as coagulant aid along with Al2SO4; and using capping material in filter unit.